Modifying the luteal phase support in natural cycle frozen-thawed embryo transfer improves cycle outcome. (2nd November 2015) - Haas, Jigal; Lantsberg, Daniel; Feldman, Noa; Manela, Daphna; Machtinger, Ronit; Dar, Shir; Rabinovici, Jaron; Orvieto, Raoul
Abstract: With the recent trend toward single embryo transfer (ET), cryopreservation of extraneous embryos is becoming increasingly prevalent. Several replacement protocols for frozen-thawed ET (FET) exist, with no advantage of one protocol over the others. All consecutive patients undergoing natural cycle Day-3 FET cycles between May 2012 and March 2015 in our IVF unit were evaluated. While following spontaneous ovulation, all patients received progesterone luteal support. Since June 2014, patients underwent the same aforementioned natural cycle FET cycles, with two additional injections, one of recombinant hCG (250 mcg) and the other of GnRH-agonist (triptorelin 0.1 mg), on the day of transfer and 4 d later, respectively. While the patients' clinical characteristics, the prevalence of embryos that survived the thawing process and the number of embryos transferred were comparable between the earlier as compared with the later period, implantation rate, positive β-hCG, clinical, and ongoing pregnancy rates were significantly higher during the later period. We, therefore, suggest that when natural cycle FET is offered, the addition of two injections of recombinant hCG and GnRH-agonist, on the day of transfer and 4 d later, respectively, might increase clinical pregancy rates. Further large prospective studies are needed to elucidate the aforementioned recommendation prior to its routine implementation. Chinese abstract: 现在的趋势倾向于单胚胎移植（ET），剩余胚胎冷冻变得更加主流。几个现存的冻融胚胎移植（FET）替代方案，没有一个与其他方案比更有优势。评估了在2012年5月到2015年3月所有在我们IVF中心的自然周期的患者第3天FET。此后自发性排卵的所有患者接受黄体酮黄体支持。从2014年6月，患者以相同上述自然周期FET，增加2次注射，移植日注射重组hCG（250 mcg），4天后注射GnRHa (曲普瑞林0.1 mg)。同时患者的临床特点，复苏胚胎存活率和移植的胚胎数在早期和晚期是可比的。植入率， β -hCG阳性率，临床妊娠率和持续妊娠率后期明显增高。因此我们建议当应用自然周期FET时，增加移植日注射重组hCG和4天后注射GnRHa，可能会提高临床妊娠率。在常规使用前，需要进一步的大型前瞻性研究。